The Conceptual LeanPPD Model - Al-Ashaab, Ahmed; Shehab, Essam; Alam, Rahman; Sopelanad, Amaia; Sorli, Mikel; Flores, Myrna; Taisch, Marco; Stokic, Dragan; James-Moore, Mike (Cranfield University, 2012)
This paper is presenting the conceptual Lean Product and Process Development (LeanPPD) model which is a project funded by the EU-PF7. The project is addressing the needs of European manufacturing companies of a new model that goes beyond lean manufacturing, to ensure the transformation of the enterprise into lean environment. This is a respond to the market demand of value creation, incorporating sustainability and customisation as well as ensuring business growth through the development of high quality products in a cost effective manner at the shortest time. The authors believe that significant change in enterprise performance can be achieved through the adoption of lean thinking throughout the product life cycle. The paper presents the LeanPPD enablers which represent the building block of the model.
Keywords: LeanPPD, Lean Thinking, KBE, SBCE, value creation